Influence of Geomagnetic Activity on Derivation of Temperatures From Meteor Wind Radars. Issue 11 (12th November 2020) - Hall, C. M.; Johnsen, M. G.
Abstract: Echoes from meteor trails can be analyzed to derive diffusion coefficient and thereafter estimates of neutral temperatures, typically around 90 km altitude. The method entails some assumptions and, usually, use of model pressures. Even so, variations in derived temperatures have been assumed to be representative and indicators of other mesospheric processes. However, we now find that the observed variations, seen as enhancements, are very closely associated with enhancements in geomagnetic activity. Here we introduce a metric for describing geomagnetic activity (as an alternative to, e.g., the k ‐index) and suggest a methodology for near‐real‐time correction of results. Plain Language Summary: It is possible to estimate upper air temperatures by observing expansion of meteor trails (akin to condensation trails from jet aircraft). We show that strong geomagnetic activity can result in wrong estimates. Key Points: Mesospheric temperatures determined by meteor wind radar Geomagnetic disturbances give rise to incorrect determination